The Impact of Our Personality on Others: The Lithuanian Comprehensive Lexical Taxonomy of Social Effects - Volungevičienė, Ana; Mlačić, Boris; Gorbaniuk, Oleg (Frontiers in Psychology, 2022)
Social effects represent the psychological (emotional, cognitive, and motivational) reactions evoked in other people by the expression of traits in behavior and emotion. From the transactional view on personality, studying the psycholexical structures of social effects can help to discover unique vs. common thought and behavior patterns, affects, and motivations, which are primarily related to personality dispositions. Thus, we developed the comprehensive taxonomy of social effects following the principles of the psycholexical approach. In the first study, two judges selected 9,625 person-descriptive terms – adjectives, type-nouns, attribute-nouns, and participles – from the Dictionary of the Standard Lithuanian Language. In the second study, six judges classified all the selected descriptors using German psycholexical methodology. Finally, a principal component analysis was performed, followed by varimax rotation for the 208 social-effect descriptors, separately for ipsatized self-ratings and observer-ratings from 203 and 204 Lithuanian students, respectively. We found out that the five-component solution was the best fit for self-ratings, whereas for observer-ratings it was a four-component structure. In this paper, we present the results from the factor analyses and discuss our findings in the context of previous studies, as well as cross-language personality models.